Hopfield neural network computation as an alternative solution for solving economic dispatch in power system - Melaty, Amirruddin; Abdullah Asuhaimi, Mohd Zin (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/